Controversies over human health and ecological impacts of glyphosate: Is it to be banned in modern agriculture?. (August 2020) - Meftaul, Islam Md.; Venkateswarlu, Kadiyala; Dharmarajan, Rajarathnam; Annamalai, Prasath; Asaduzzaman, Md; Parven, Aney; Megharaj, Mallavarapu
Abstract: Glyphosate, introduced by Monsanto Company under the commercial name Roundup in 1974, became the extensively used herbicide worldwide in the last few decades. Glyphosate has excellent properties of fast sorption in soil, biodegradation and less toxicity to nontarget organisms. However, glyphosate has been reported to increase the risk of cancer, endocrine-disruption, celiac disease, autism, effect on erythrocytes, leaky-gut syndrome, etc. The reclassification of glyphosate in 2015 as 'probably carcinogenic' under Group 2A by the International Agency for Research on Cancer has been broadly circulated by anti-chemical and environmental advocacy groups claiming for restricted use or ban of glyphosate. In contrast, some comprehensive epidemiological studies involving farmers with long-time exposure to glyphosate in USA and elsewhere coupled with available toxicological data showed no correlation with any kind of carcinogenic or genotoxic threat to humans. Moreover, several investigations confirmed that the surfactant, polyethoxylated tallow amine (POEA), contained in the formulations of glyphosate like Roundup, is responsible for the established adverse impacts on human and ecological health. Subsequent to the evolution of genetically modified glyphosate-resistant crops and the extensive use of glyphosate over the last 45 years, about 38 weed species developed resistance to this herbicide. Consequently, its use in the recent years has been either restricted or banned in 20 countries. This critical review on glyphosate provides an overview of its behaviour, fate, detrimental impacts on ecological and human health, and the development of resistance in weeds and pathogens. Thus, the ultimate objective is to help the authorities and agencies concerned in resolving the existing controversies and in providing the necessary regulations for safer use of the herbicide. In our opinion, glyphosate can be judiciously used in agriculture with the inclusion of safer surfactants in commercial formulations sine POEA, which is toxic by itself is likely to increase the toxicity of glyphosate. Graphical abstract: Image 1089 Highlights: Reports on toxicity of glyphosate established in humans seem to be inconsistent. Glyphosate alone is non-toxic or extremely less toxic even to higher animals. Surfactants in formulations like POEA and MON 0818 are more toxic than glyphosate. Developing safe, economical and effective surfactants is the best alternative. Glyphosate could be judiciously used in agriculture without restrictions or banning.